The risk of tuberculosis in patients with psoriasis treated with anti-tumor necrosis factor agents - SEÇKİN GENÇOSMANOĞLU, DİLEK; ERGUN, SAFİYE ATLAS TÜLİN; KARAKURT, SAİT; ÖZGEN, ZÜLEYHA (WILEY-BLACKWELL, 2015)
BackgroundTumor necrosis factor-alpha (TNF-) antagonist treatment is associated with 1.6 to 27 times higher risk of tuberculosis (TB). ObjectiveTo find TB incidence of psoriasis patients treated with TNF- antagonists and define risk factors related with this condition in a country with moderately high risk of TB. MethodsThree hundred seventy psoriasis patients treated by anti-TNF agents in four referral centers were included. The data on the characteristics of the patients, TB history, tuberculosis skin test results, anti-TNF agent type and exposure time, localization of TB, and isoniazide prophylaxis state were analyzed. ResultsFour patients (1.08%) developed TB, three pulmonary and one gastrointestinal, 2-23months after initiating anti-TNF agents. Other than the patient with gastrointestinal TB, who was using methotrexate and corticosteroid concomitantly, none had contributing risk factors for TB. Two patients developed pulmonary TB in spite of chemoprophylaxis. Three patients with pulmonary TB completely recovered following antiTB treatment whereas patients with gastroinrestinal TB developed renal failure. LimitationsThe major limitation of the study is the lack of a diseased control group, which enables us to compare the risk of psoriatics with that of patients having other inflammatory diseases. ConclusionTuberculosis is a rare but a severe complication of anti-TNF treatment and may develop in spite of chemoprophylaxis. The risk of TB in psoriasis patients in the present study is comparable to literature mostly based on rheumatology patients.
Keywords: ANTI-TNF THERAPY; RHEUMATOID-ARTHRITIS; SKIN-TEST; INFECTION; ANTAGONISTS; INFLIXIMAB; BIOLOGICS; REGISTRY; DISEASE; ASSAYS